KAJIAN KEMAMPUAN SELF-EFFICACY MATEMATIS SISWA DALAM PEMECAHAN MASALAH MATEMATIKA - Alifia, Nugrahaning Nisa; Rakhmawati, Intan Aulia (Jurnal Pembelajaran Matematika, 2018)
Abstract: Self-efficacy is related to a person's judgment of student ability to solve something. This ability to be one that supports the successful completion of the task well, it can be said that self-efficacy support students' mathematical abilities. This ability becomes a powerful predictor of problem solving. This article aims to examine students' mathematical self-efficacy abilities in mathematical problem solving. The method used is to collect the data library without empirical test. Self-efficacy is important role in everything, especially for students who are solto solve mathematics problem. Given the high self-efficacy capability in the student is expected to succeed in solving mathematics problem. Students with high mathematical self-efficacy are better able to solve mathematical problems well and student failures in solving mathematical problems are assumed for lack of effort or learning. Conversely, students with low mathematical self-efficacy tend to be vulnerable and easily give up in solving mathematical problems and student failures in solving mathematical problems are assumed for their lack of mathematical ability.Keywords: Problem Solving, Self-Efficacy.